The last olympian - Riordan, Rick. (New York Scholastic Inc., 2009)
The long-awaited prophecy surrounding Percy Jackson's sixteenth birthday unfolds as he leads an army of young demigods to stop Kronos in his advance on New York City, while the Olympians struggle to contain the rampaging monster, Typhon.
Originally published: New York : Hyperion Books for Children, c2009.
Keywords: Mythology, Greek -- Juvenile fiction; Fate and fatalism -- Juvenile fiction; Monsters -- Juvenile fiction; Animals, Mythical -- Juvenile fiction; Titans (Mythology) -- Juvenile fiction